Survival Strategies and Emotions. Informal Union and Marriage on the Pacific Slope of Colonial Central America - Castellón Osegueda, José Ricardo (2021)
The purpose of this article is to examine how survival needs shaped the behavior of the inhabitants of the interior of the Central American Pacific region between the second half of the 18th century and the end of the colonial era, a period of particular social and geographical mobility. For this, information obtained from Central American archives is analyzed through the lens of survival strategies, unions (formals or not) as a resource and the role of emotions in the process. As a result of this research, it is deduced that affective (emotions) and biological (reproductive capacities) components, until now little treated by Central American historiography, were key elements in the development of Central American colonial society.